Osmotic shock induction of capsule synthesis in Escherichia coli K-12. - Sledjeski, D D (1996)
The genes (cps) involved in the synthesis of the colanic acid capsular polysaccharide in Escherichia coli K-12 are transcriptionally regulated by numerous proteins. Two of these, RcsB and RcsC, share homology with two-component regulatory elements that respond to environmental stimuli. Osmotic shock by sucrose or NaCl transiently increased transcription of a cpsB::lacZ fusion. RcsC and RcsB were essential for osmotic induction of colanic acid synthesis. In contrast to observations in some other osmotically regulated systems, addition of glycine betaine enhanced the osmotic induction of cps::lacZ by both sucrose and NaCl but had no effect alone.